Application of the Fenton-like agent based on magnetic iron and manganese oxide in the degradation process of paracetamol in water (Mongolian Journal of Chemistry, 2023)
A Fenton-like catalyst MnO2-Fe3O4/SiO2 is synthesized via a two-step approach. The prepared composite has a mesoporous structure and a high surface area of 190 m2/g. The XRD pattern describes a specific peak of Fe3O4 magnetite on the baseline of amorphous silica. Furthermore, the FTIR spectra not only show the height assigned to stretching vibrations of Si-O-Si bonds, and Fe–O–Fe connections but also exhibit a small peak that matches the Mn–O bonds. SEM images exhibit a porous network structure of the composites with some holes among 30 – 100 nm clusters. The activity of the catalyst is determined in a paracetamol degradation as a Fenton oxidation. The paracetamol removal efficiency is at 85.6% with the optimal condition as initial pH 3, catalyst dosage of 0.15 g/50mL and H2O2 concentration of 1 mL/50 mL. In addition, the catalyst can be reused at least 5 times with a low reduction of the catalytic activity from 85.6% to 80.8%. The experiment results open a direction that has high efficiency in the treatment process of excess paracetamol in pharmacy wastewater.